Perancangan Sistem Informasi Penjualan Warung Ayam Geprek Ramane Berbasis Website - Dias Ayu Budi Utami; Anan Widianto (Yayasan Literasi Sains Indonesia, 2022)
With the rapid development of technology, business competition is increasingly racing in utilizing technology. Even micro business entities such as MSMEs have penetrated into computerized systems to process data. One of the MSMEs that will change the system from a manual system to a computerized system is Warung Ramane which is an MSME engaged in the food and beverage sector, but the MSMEs are still using a manual system, starting from the sales transaction process that is still written into the sales book which causes slow search. data, as well as the preparation of sales reports which are still done manually. This causes the preparation of sales reports that take a long time because of the large amount of data that must be processed and causes human errors, such as report writing errors, reports that are not neatly arranged, and errors in calculating the amount of turnover or profits obtained. From the above problems, the solution offered is the design of a website-based sales information system at Ayam Geprek Warung Ramane using the waterfall system development method, so that it can reduce human error problems and make it easier to search for data or archives and sales reports can be faster. With this information system, the owner can find out what food or beverage menus are the most sold/sold, and which ones are the least sold, and find out the level of sales for each certain period contained in the sales report, so that MSMEs can analyze and evaluate the menu. for sale